O encontro reflexivo como prática de atenção psicoeducativa junto a mulheres-mães: perspectivas dialógicas na educação dos filhos - Vezneyan, Mariam Deborah Santos (2011)
This work s objective has been to understand Reflexive Meetings, carried out with women-mothers as an experiment in psycho-educational care, in a dialogical education perspective. A qualitative study of interventional character was carried out as part of a comprehensive research project the Articulation and Dialogue Project with the aim of following the construction process of projects articulated among different educational contexts, within a community located in the outskirts of the city of São Paulo. The research situation is constituted by the observation and participation in 3 Reflexive Meetings, which were recorded, transcribed, read, and re-writen, thus originating 3 reference texts, designated as meeting descriptions. Subsequently, the units of meaning of all descriptions were sought out and grouped into constellations , and analyzed according to Paulo Freire s theoretical framework. The analysis revealed that the world experienced during childhood by those women-mothers (most of which were born in the Brazilian Northeast), was characterized by survival challenges and by the authoritarian educational practices that were utilized by their families of origin. The world experienced at present by the women-mothers also places before them great challenges, chiefly due to the lack of financial resources and the situation of vulnerability in which their children find themselves: drugs, sexuality, early pregnancy, pedophilia, as well as the influence of the media and virtual world technologies. The women-mothers endeavor to use educational practices that are different from those with which they were raised, and they triy to protect their children by means of affectivity and dialogue, although they encounter some difficulties to talk/act, especially when the issues involve the theme of sexuality. The analyzed Reflexive Encounters can be understood, then, as an endeavor in psycho-educational care, in as much as the discussions, experience sharing and reflections that the women-mothers carried out regarding the challenges inherent to the responsibility of educating their children comprised an experience of dialogue and pointed to educational practices in a dialogical perspective